PENGEMBANGAN MODEL PERTUNJUKAN MUSIK BERBASIS WORK FROM HOME DENGANPEMANFAATAN TEKNOLOGI DIGITAL SEBAGAI DAMPAK COVID-19 - Sinaga, Theodora -; -, Suharyanto - (Universitas Negeri Medan, 2020)
This research aims to produce an effective performance method based on work from home with the application of digital music technology due to the impact of Covid 19. This method is useful for musicians, lecturers, academics and the public that can be used as entertainment, education, watching and good guidance in this modern era. The purpose of this study consists of: 1) Helping musicians, composers, singers, conductors, teachers, academics to make it easier to understand the use of digital technology for the needs of creative music performances that are work from home; and 2) Finding a model for developing creative music performances based on digital technology to accelerate the ability to play, collaborate, educate and express skills that are work from home. The method used in this research is a qualitative approach. Data observations were carried out as a first step to finding references to digital music based music performances that became the raw material for applying the development model. Data was collected through video recording of both live and offline shows in various reference sources. In between, an interview with musicians is also needed to enrich the supporting terms and features. The output of this research is in the form of scientific articles in national and international accredited journals, video and audio products in the form of application of digital music and intellectual property software. This research can be a finding that contributes to the development of creative music performances in North Sumatra. This research is also expected to contribute to uncover the development of the demonstration model through digital technology media.